Some Physical Properties of 9-Year-Old Xylia xylocarpa Planted in Malaysia - Sahri, Mohd Hamami; Josue, James; Su, Kyoung Chun (2008)
Xylia xylocarpa is fast-growing trees that are currently planted on trial basis in Sabah, Malaysia. The wood quality of trees grown in Sabah may differ from those grown in other places due to the environmental factors. Five 9-year-old trees of each species were extracted from their respective plots at Luasong, Tawau. Wood specimens were prepared from three height levels; bottom, middle and top, at the inner and outer radial positions. The within-tree and between-tree variations of physical properties of these species were analyzed. The basic density, oven-dry density and green moisture content (MC) are 0.72 g/㎤, 0.78 g/㎤ and 49.8% respectively. The shrinkage from green to oven-dry conditions for the radial and tangential directions were 3.35% and 5.76%, respectively. The trends of within-tree variations for most properties were more consistent in radial rather than vertical direction. This suggests diameter growth to be a more important factor contributing to the variations compared to height. Samples from the outer part of the stem were found to have higher density, shrinkage and mechanical strengths. The between-trees variations of some wood properties were found to be significantly different, probably due to genetic and micro-environmental factors. Significant correlation was recorded among the physical properties of the species. The true potential of X. xylocarpa for end-uses would be enhanced by further research such as the study on properties of wood from different sites and other properties like durability, seasoning, processing and machining characteristics. The characteristics of X. xylocarpa are comparable to a number of local popular hardwood species, indicating its suitability for heavy construction uses.